KEBIJAKAN PENDIDIKAN KEWARGANEGARAAN ERA REFORMASI DI INDONESIA - Samsuri . (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Civic Education Policy in the Reform Era in Indonesia. This paper presents a preliminary study on civic education in the national educational policy during the reform era since 1998 in Indonesia. The reform movement has impacts on the reform of national education. Civic education has entered the changing paradigm to build good citizens. In the old paradigm, civic education mainly served the political regime hegemony. Civic education was reduced to value or character education per se. The politics of education in the new era has shifted the paradigm of civic education into the standardization according to democratic citizenship education norms. Civic education focuses more on how the competent teachers transform democratic values democratically. Keywords: reform, civic education, politics of education